The desire for recognition: the hostile foreign other in American foreign policy - Liu, Zonghan (Nanyang Technological University, 2023)
The concept of an enemy has played a crucial role in shaping American foreign policy, as evident from numerous international events throughout American history. This article examines the importance of the existence of a hostile foreign “Other” in confirming the American sense of “Self” as a great and good nation and its manifestation in American foreign policy. Drawing on the political-philosophical concept of the “desire for recognition” in the politics of recognition, as proposed by the Princeton political scientist Francis Fukuyama, this article demonstrates how the political ideal of American democracy, with its emphasis on an egalitarian society, contributes to Americans’ sense of exceptionalism and their Manichean outlook that splits the world into opposing spheres of good and evil, as well as forces the United States to construct its foreign policy around the menace of an evil enemy to protect its democratic ideal.